2019
DOI: 10.1175/bams-d-18-0037.1
|View full text |Cite
|
Sign up to set email alerts
|

The Northern California Wildfires of 8–9 October 2017: The Role of a Major Downslope Wind Event

Abstract: A series of large wildfires began over the terrain north of San Francisco, California, during the evening of 8 October 2017 and spread across nearly 250,000 acres, including areas near the towns of Santa Rosa and Napa. These “Wine Country” wildfires were the most destructive in California history, with 44 deaths; the loss of 9,000 buildings; damage to approximately 21,000 structures; $10 billion of insured losses; and substantially greater total economic loss. This paper describes the synoptic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…For PM2.5, there is no chronic or acute REL value set by the California OEHHA, but PM2.5 is a criteria air pollutant and is therefore regulated by the USA EPA through implementation of NAAQS. As shown in Figure 5, 24-h average PM2.5 concentrations were generally below the 24-h NAAQS threshold of 35 µ g/m 3 , except for a period in October 2017 that was coincident with the Northern California wildfire [46]. A similar peak was observed for BC concentrations during that period (as well as for benzene, as discussed in Section 3.1.3).…”
Section: Pm25 and Black Carbonsupporting
confidence: 52%
See 1 more Smart Citation
“…For PM2.5, there is no chronic or acute REL value set by the California OEHHA, but PM2.5 is a criteria air pollutant and is therefore regulated by the USA EPA through implementation of NAAQS. As shown in Figure 5, 24-h average PM2.5 concentrations were generally below the 24-h NAAQS threshold of 35 µ g/m 3 , except for a period in October 2017 that was coincident with the Northern California wildfire [46]. A similar peak was observed for BC concentrations during that period (as well as for benzene, as discussed in Section 3.1.3).…”
Section: Pm25 and Black Carbonsupporting
confidence: 52%
“…The 8-h average concentrations for benzene exceeded the REL in a few instances over the 3-year study period as shown in Figure S2. One of such periods (October 2017) was coincident with the Northern California wildfire [46], which resulted in significant deterioration of air quality across the region. Similarly, the 1-h average concentrations of benzene, which were predominantly below the corresponding REL at all community locations ( Figure 2), exhibited two exceedances at the PR site during this period (9 October 2017 and 10 October 2017).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Simple statistical approaches quantifying relationships between wind and PM 2.5 in the presence and absence of pollution sources (e.g., wildfire), could be particularly useful to help in forecasting and identifying wildfire‐generated PM 2.5 . The same approach used here could be extended to other downslope wind systems in California and elsewhere, which also spread wildfires, for example, Diablo winds of Northern California (Mass & Ovens, ; Smith et al, ). Specific wind systems, and wind data in general, could also serve as the link between wildfire smoke PM 2.5 and wildfire risk in climate change scenarios (Westerling, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study has three aims: (1) it identifies limitations in the development of fire prediction models using cellular automata; (2) it suggests a solution to these limitations and implements an example prototype as a preliminary approach, concentrating on the functionality of fire propagation prediction in detail using geographical information system (GIS) software; and (3) it proposes an efficient strategy of evacuation guidance from wildfires. In particular, the last aim is important because there is a trade-off between quality of prediction and the performance speed of fire calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, wildfires have devastated lives and properties. For instance, a state-wide, fire cost the lives of 44 people and devastated about 100,000 hectares in California, USA in 2017 [1]. In Portugal in the same year, there were more than 62 casualties in the forest fire of Pedrógão Grande area [2].…”
Section: Introductionmentioning
confidence: 99%